On the use of a single-fiber multipoint plastic scintillation detector for (192)Ir high-dose-rate brachytherapy - Therriault-Proulx, François (American Association of Physicists in Medicine, 2013)
Purpose: The goal of this study was to prove the feasibility of using a single-fiber multipoint plastic scintillation detector (mPSD) as an in vivo verification tool during (192)Ir high-dose-rate brachytherapy treatments. Methods: A three-point detector was built and inserted inside a catheter-positioning template placed in a water phantom. A hyperspectral approach was implemented to discriminate the different optical signals composing the light output at the exit of the single collection optical fiber. The mPSD was tested with different source-to-detector positions, ranging from 1 to 5 cm radially and over 10.5 cm along the longitudinal axis of the detector, and with various integration times. Several strategies for improving the accuracy of the detector were investigated. The device's accuracy in detecting source position was also tested. Results: Good agreement with the expected doses was obtained for all of the scintillating elements, with average relative differences from the expected values of 3.4 ± 2.1%, 3.0 ± 0.7%, and 4.5 ± 1.0% for scintillating elements from the distal to the proximal. A dose threshold of 3 cGy improved the general accuracy of the detector. An integration time of 3 s offered a good trade-off between precision and temporal resolution. Finally, the mPSD measured the radioactive source positioning uncertainty to be no more than 0.32 ± 0.06 mm. The accuracy and precision of the detector were improved by a dose-weighted function combining the three measurement points and known details about the geometry of the detector construction. Conclusions: The use of a mPSD for high-dose-rate brachytherapy dosimetry is feasible. This detector shows great promise for development of in vivo applications for real-time verification of treatment delivery.